Treatment of Dye Wastewater from Batik Industry by Coconut Shell Activated Carbon Adsorption - Aulia Qisti; Yudhi Utomo; Deni Ainur Rokhim (Jurnal Kimia Fullerene, 2021)
Batik is a characteristic Indonesian textile product. The color of batik is one component that affects the quality of batik. Various types of batik dyes, one of which is remazol dyes. Remazol dyes are synthetic dyes that have strong chemical bonds. This is what underlies the process of production of the household batik industry in the village of Purwosekar, District of Tajinan, Malang Regency, with remazol coloring will produce liquid waste that is difficult to be deciphered naturally. This study aims to provide a water treatment solution using the coconut shell activated carbon adsorption method with chemical activation and the ability to adsorb remazol dyes. Adsorption experiments were carried out in batches with a mesh size of 8 with coconut shell carbon activated with 1 M HCl solution for 24 hours. The absorption of remazol dyes by coconut shell activated charcoal is carried out with a stirring speed variation for 60 minutes and the mass of activated charcoal to find the optimum adsorption conditions. Stirring speed variations are 30 rpm, 60 rpm, and 90 rpm, resulting in the highest efficiency at a speed of 90 rpm. While the variations in mass are 200 grams and 300 grams, the highest efficiency is obtained with a mass of 300 grams. Thus, the efficiency of the coconut shell activated carbon is proportional to the stirring speed and mass of the coconut shell activated carbon used